Introduction to the Special Issue on New Longitudinal Data for Retirement Analysis and Policy. (October 2021) - Angrisani, Marco; Samek, Anya; Kapteyn, Arie
Abstract : The number of data sources available for academic research on retirement economics and policy has increased rapidly in the past two decades. Data quality and comparability across studies have also improved considerably, with survey questionnaires progressively converging towards common ways of eliciting the same measurable concepts. Probability-based Internet panels have become a more accepted and recognized tool to obtain research data, allowing for fast, flexible, and cost-effective data collection compared to more traditional modes such as in-person and phone interviews. In an era of big data, academic research has also increasingly been able to access administrative records (e.g., Kostøl and Mogstad, 2014; Cesarini et al ., 2016), private-sector financial records (e.g., Gelman et al ., 2014), and administrative data married with surveys (Ameriks et al ., 2020), to answer questions that could not be successfully tackled otherwise.